2020
DOI: 10.1021/acssensors.9b02585
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Monitoring, Sampling, and Sensing Techniques for Bioaerosols in the Atmosphere

Abstract: Bioaerosols in the form of microscopic airborne particles pose pervasive risks to humans and livestock. As either fully active components (e.g., viruses, bacteria, and fungi) or as whole or part of inactive fragments, they are among the least investigated pollutants in nature. Their identification and quantification are essential to addressing related dangers and to establishing proper exposure thresholds. However, difficulties in the development (and selection) of detection techniques and an associated lack o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 109 publications
0
29
0
Order By: Relevance
“…Recently, use of high‐throughput sequencing has led to the exploration of the vast community structure and diversity of the indoor microbiome of the built environment that was previously uncharacterized and unrecognized [23]. All the organisms (including microorganisms) are driven by a plethora of interconnected biotic as well as abiotic factors and processes that further decide their adaptive strategies for survival and proliferation in the particular environmental situation.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, use of high‐throughput sequencing has led to the exploration of the vast community structure and diversity of the indoor microbiome of the built environment that was previously uncharacterized and unrecognized [23]. All the organisms (including microorganisms) are driven by a plethora of interconnected biotic as well as abiotic factors and processes that further decide their adaptive strategies for survival and proliferation in the particular environmental situation.…”
Section: Introductionmentioning
confidence: 99%
“…ATP bioluminescence-based sensors have also been used to detect the location and density of several air-borne bacteria in both artificially created and natural bioaerosols in indoor environments. 246 The biosensors reported have either used fabricated paper disks immobilised with luciferase/D-luciferin or sensors microfluidic chips. 247,248 Air was vented into and bubbled into a bio-sampler bottle containing 20 mL of deionised water to capture any cells found in the air.…”
Section: Mapping Pollution In Ecosystemsmentioning
confidence: 99%
“…The research revealed a bat vector that has transmitted coronavirus to humans [68], [69]. Bio-aerosols microscopic airborne particles pose widespread human and animal threats [70]. The researchers have presented an analysis of the SARS-CoV 2 transmission theory from a list of animals that sold avian, swine, phocine, bovine, canine, seafood, frogs, camels, etc.…”
Section: Fig 3 Transmission Concepts For Covid-19 Virus From Human'mentioning
confidence: 99%